2020
DOI: 10.1371/journal.pone.0238618
|View full text |Cite|
|
Sign up to set email alerts
|

Accessing Take-Home Naloxone in British Columbia and the role of community pharmacies: Results from the analysis of administrative data

Abstract: Introduction British Columbia's (BC) Take-Home Naloxone (THN) program provides naloxone to bystanders for use in cases of suspected opioid overdose. This study seeks to provide trends and analysis from the provincial BC THN program since inception in 2012 to the end of 2018. Materials and methods BC THN shipment and distribution records from 2012-2018 were retrieved. Frequency distributions were used to describe characteristics of individuals accessing the program. To evaluate correlates of distribution after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
(19 reference statements)
2
17
0
Order By: Relevance
“…Reports on refills in relation to participants is not a commonly presented measure, however Enteen et al (41) found that 24% returned for refill, which is similar to our result. Proportion of naloxone having been used for overdose reversal, in relation to all cause refills, varied between 39-69% (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on refills in relation to participants is not a commonly presented measure, however Enteen et al (41) found that 24% returned for refill, which is similar to our result. Proportion of naloxone having been used for overdose reversal, in relation to all cause refills, varied between 39-69% (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The province has also experienced a decline in visits to OPS/SCS during the COVID-19 pandemic, which further increases risks of adverse outcomes from overdose [ 30 ]. Take Home Naloxone kits are widely available to community members throughout BC [ 12 , 13 ], but the FORB program improves access to naloxone in BC by providing a dedicated supply of naloxone and protective equipment including CPR face shields, gloves, and staff training supplies for use by non-healthcare service providers in the workplace where there is a risk of overdoses on site [ 14 , 15 ].This further eliminates challenges that may be encountered by community agencies that may have not have allocated budgets or capacities to source these supplies. Having these resources readily available helps non-healthcare service providers in being prepared and supported to respond to overdoses.…”
Section: Discussionmentioning
confidence: 99%
“…The BC THN program, which launched in 2012, was rapidly expanded in response to increasing overdose fatalities in 2016 [10][11][12][13]. Although the BC THN program was widely available across BC, the THN kits and supplies are not intended for occupational purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In December 2017, the BC THN program was rolled out in community pharmacies, also at no charge, greatly increasing access to kits, especially in remote regions [ 20 ]. Prior research indicates that people who are not personally at risk of overdose are more likely to obtain kits from pharmacy sites, especially when collecting a naloxone kit for the first time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%